Use of Variable Matrices of Land Cover Changes for the Assessment of Land Dynamics Based on the Indicators of Land Degradation Neutrality - Kust German; Lobkovskiy Vasiliy; Lobkovskaya Ludmila; Podlesnov Vladimir; Movchan Michail; Antipova Anna (Russian Journal of Earth Sciences)
The article presents the results of land degradation assessment for the Ryazan and Tula regions based on the concept of land degradation neutrality (LDN). For the first time the approaches were demonstrated for developing a methodology for assessing LDN sub-indicators for humid areas (using the moving average method and modified matrices of changes in land cover type). For forest lands, a matrix modified to take into account the dynamics of woody vegetation, including mutual transitions of coniferous, broad-leaved and small-leaved forests, is proposed. New data on land degradation trends for the studied territories were obtained. The possibility of using the LDN methodology to update official statistics, detail land productivity trends and land use changes is confirmed. Despite the decrease in the degradation rate, in the considered territories, degraded and moderately degraded lands in total still significantly prevail over improved ones, which requires active intervention in regulating land use conditions and the use of new methods. At the same time, the situation in the regions is somewhat different: if in the Tula region degraded lands are mainly confined to the forest-steppe subzone, then in the Ryazan region, foci of degraded lands are equally often found in forest areas. A high dependence of land degradation trends on even short-term (within 5–10 years) climate changes has been revealed. For the Ryazan and Tula regions, such reactions (improvement or deterioration) in individual areas and in the region as a whole can be very contrasting, which requires special consideration when developing measures to adapt to climate change.